The humanization of care and the role of the multiprofessional team in the recovery of patients interned in Adult Intensive Care Units: A literature review (Research, Society and Development, 2022)
Objective: To investigate the strategies used by the multidisciplinary team to humanize care and the role of this team in the recovery of critical patients. Methodology: This is a systematic literature review, based on scientific articles found in Pubmed, Scielo and Google Scholar. Results: Initially, 52 articles were selected, of which 22 constituted analysis material for the elaboration of this work and 30 were excluded because they did not fit the inclusion criteria. Among the selected articles, 12 presented results used in the elaboration of the discussion of this review. Conclusion: Humanization in ICUs is seen as a way to rescue the human dignity of critical patients and this should be, as much as possible, contemplated in its entirety so that there is a significant improvement in their quality of life. However, it is still necessary to expand the analysis of this theme through the realization, discussion and dissemination of more studies that can contribute to the expansion of this very relevant theme, especially in the areas of professional training and continuing education in service.